2019
DOI: 10.31234/osf.io/jzhuk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Stereotype Threat Affect Men in Language Domains?

Abstract: Currently, boys and men tend to underperform in language domains in school and on standardized tests, and they are also underrepresented in language-related fields of study. Stereotype threat is one way in which psychologists have found that stereotypes can affect students’ performance and sense of belonging in academic subjects and test settings Researchers have traditionally found that when girls and women are reminded of stereotypes that math is for boys, girls and women tend to underperform on math tests. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…In a nutshell, the more efficacious students feel about their learning due to their gender stereotypes, the more likely they are to engage with and attain their language learning and development goals. With these findings, our study expands upon previous research (Carr & Pauwels, 2006; Chaffee, Lou, & Noels, 2020; Chaffee et al., 2020; Pomerantz, 2008; Schmenk, 2004) in showing how gender stereotypes are relevant for EFL learners’ self‐efficacy and anxiety and therefore their actual language attainment.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a nutshell, the more efficacious students feel about their learning due to their gender stereotypes, the more likely they are to engage with and attain their language learning and development goals. With these findings, our study expands upon previous research (Carr & Pauwels, 2006; Chaffee, Lou, & Noels, 2020; Chaffee et al., 2020; Pomerantz, 2008; Schmenk, 2004) in showing how gender stereotypes are relevant for EFL learners’ self‐efficacy and anxiety and therefore their actual language attainment.…”
Section: Discussionsupporting
confidence: 79%
“…Second, due to the correlational nature of the results, no causation can be inferred. Researchers seeking a causal explanation should adopt an experimental approach such as using stereotype threat manipulations (e.g., Chaffee et al., 2020; Keller, 2007) and investigate the effects of gender stereotypes on EFL achievement accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many scholars have cautioned that there is not enough rigorous evidence that stereotype threat is the primary cause of intergroup differences in test performance (Sackett et al, 2004; Shewach, Sackett, & Quint, 2019). Their critique, combined with studies providing disconfirming evidence (e.g., Chaffee, Lou, & Noels, 2020), raises concerns about the validity of how stereotyped threat is evoked and then reflected in subsequent outcomes.…”
Section: Assessment In Action: Using 3e Criteria To Evaluate Sttmentioning
confidence: 99%
“…The studies in question include several meta-analyses (Flore & Wicherts, 2015;Stoet & Geary, 2012), a number of large, pre-registered replications (Finnigan & Corker, 2016;Flore et al, 2019), and an analysis of 5.5 million chess games played in international tournaments, which found that women's performance was better, rather than worse, under conditions of stereotype threat (Stafford, 2018). Meanwhile, on the other side of the ledger, a recent study failed to replicate the finding that stereotype threat impairs men's performance on tests of language ability (Chaffee et al, 2019). At the very least, the effects of stereotype threat are more modest and situationally contingent than was originally assumed.…”
Section: The Nature and Nurture Of Sex Differences In Cognitive Aptitmentioning
confidence: 99%